2017
DOI: 10.1021/acs.jpclett.7b01779
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Polymerization and Disproportionation of Li2C2 Accompanied with Irreversible Conductivity Enhancement

Abstract: LiC has the highest theoretical capacity (1400 mA·h·g) as the electrode material for Li-ion battery, but suffers from low conductivity. Here we found that under external pressure its conductivity was irreversibly enhanced by 10-fold. To explain that, we performed X-ray diffraction, Raman, IR, gas chromatography-mass spectrometry, and theoretical investigations under external pressure. We found that the C anions approached to each other and polymerized upon compression, which is responsible for the irreversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…By comparing the experimental result of Li2C2 under high pressure with the theoretical calculated IR spectra, the carbon-ribbon structure in the Li2C2 polymeric product was identified, and many advanced hydrocarbons in the hydrated products of the recovered sample were detected by GC-MS, which also supports the addition PIP of C2 2− , and the ribbon structures (Figure 3a) [32]. However, different from CaC2, there were a portion of products with the C:H ratio significantly deviating from 1:1, which revealed the occur- By comparing the experimental result of Li 2 C 2 under high pressure with the theoretical calculated IR spectra, the carbon-ribbon structure in the Li 2 C 2 polymeric product was identified, and many advanced hydrocarbons in the hydrated products of the recovered sample were detected by GC-MS, which also supports the addition PIP of C 2 2− , and the ribbon structures (Figure 3a) [32]. However, different from CaC 2 , there were a portion of products with the C:H ratio significantly deviating from 1:1, which revealed the occurrence of the disproportionation reaction.…”
Section: Alkyne and Acetylidesmentioning
confidence: 63%
See 1 more Smart Citation
“…By comparing the experimental result of Li2C2 under high pressure with the theoretical calculated IR spectra, the carbon-ribbon structure in the Li2C2 polymeric product was identified, and many advanced hydrocarbons in the hydrated products of the recovered sample were detected by GC-MS, which also supports the addition PIP of C2 2− , and the ribbon structures (Figure 3a) [32]. However, different from CaC2, there were a portion of products with the C:H ratio significantly deviating from 1:1, which revealed the occur- By comparing the experimental result of Li 2 C 2 under high pressure with the theoretical calculated IR spectra, the carbon-ribbon structure in the Li 2 C 2 polymeric product was identified, and many advanced hydrocarbons in the hydrated products of the recovered sample were detected by GC-MS, which also supports the addition PIP of C 2 2− , and the ribbon structures (Figure 3a) [32]. However, different from CaC 2 , there were a portion of products with the C:H ratio significantly deviating from 1:1, which revealed the occurrence of the disproportionation reaction.…”
Section: Alkyne and Acetylidesmentioning
confidence: 63%
“…The acetylide anions such as C≡C 2− and HC≡C − were also predicted to polymerize into conjugated extended carbon framework with excellent electrical conductivity under HP [24][25][26][27][28][29]. As the simplest acetylides, CaC2 and Li2C2 were investigated under HP [27,[30][31][32][33], and we firstly evidenced their PIP experimentally, which resulted in a remarkable conductivity enhancement,10 7 -fold for CaC2, and 10 9 -fold for Li2C2 [31,32]. After releasing to the atmospheric pressure, due to the extended covalent conjugated C-C bonding, the high conductivity of the recovered products maintains.…”
Section: Alkyne and Acetylidesmentioning
confidence: 99%
“…Li 2 C 2 was reported to transform from Immm phase to Pnma phase and amorphized at higher pressure, which probably contains the polymerization process [61]. We made further investigation by combining the spectral measurements and theoretical prediction [64]. The IR data showed two new peaks at 1187 and 1296 cm −1 at 27 GPa (Figure 4a), which were recognized as the in-plane transverse mode and longitudinal mode of charged carbon ribbons in lithium polyacenide (Figure 4b).…”
Section: Metallic Carbidementioning
confidence: 92%
“…The more complicated reaction was observed in the PIP of lithium acetylides (Li2C2), which was accompanied by disproportionation processes. Li2C2 was reported to transform from Immm phase to Pnma phase and amorphized at higher pressure, which probably contains the polymerization process [64]. We made further investigation by combining the spectral measurements and theoretical prediction [65].…”
Section: Metallic Carbidementioning
confidence: 93%
“…Further, it has been shown that Li can be removed from Li 2 C 2 in mild oxidation reactions leading to nanopatterned carbon [14] and it has been predicted that Li 2 C 2 represents a precursor toward novel metallic and superconducting polycarbides [15,16]. This was recently partially confirmed by experiments that indicated an irreversible polymerization of C 2 units when pressurizing Li 2 C 2 to around 50 GPa [17].…”
Section: Introductionmentioning
confidence: 89%